Multi Attribute Neutrosophic Optimization Technique forOptimal Crop Selection in Ariyalur District - Angammal S; Hannah Grace G; Nivetha Martin; Florentin Smarandache (Neutrosophic Sets and Systems)
Ranking crops is a vital part of sustainable farming practices. A deliberate strategy that incorporates multi-criteria decision-making is essential for achieving sustainability in agriculture. The process of choosing crops involves a lot of unknowns and unpredictable elements. The neutrosophic set, characterized by the three independent degrees of truth (T), falsity (F), and indeterminacy (I), is more adept at handling incomplete data. The current study combines single-valued multi-criteria neutrosophic programming with the TOPSIS approach to examine the crop selection process in the Ariyalur district. This study incorporated expert advice and a thorough literature analysis to identify the fundamental criteria for developing sustainable crop planning for important crops in the Ariyalur area. In order to rate the crops and achieve sustainability for agricultural production, eleven significant criteria were selected based on environmental, social, economic, and soil nutrient concerns. In this study, the relative importance of criteria and alternatives is assessed by consolidating the views of different decision-makers into a unified opinion through a single-valued neutrosophic set-based weighted averaging operator. The current approach will greatly enhance the self-sufficiency of the agricultural sector and boost the country’s GDP. Additionally, it will support the Ministry of Agriculture and other stakeholders in formulating regulations related to crop harvesting methods.